Development and characterization of niosomal gel of fusidic acid: in-vitro and ex-vivo approaches. Issue 1 (31st December 2022) - Waqas, Muhammad Khurram; Sadia, Haleema; Khan, Muhammad Imran; Omer, Muhammad Ovais; Siddique, Muhammad Irfan; Qamar, Shaista; Zaman, Muhammad; Butt, Muhammad Hammad; Mustafa, Mian Waqar; Rasool, Naeem
ABSTRACT: Niosomes are multilamellar vesicles that efficiently deliver active substance into skin systemic circulation or skin layers. They are used in topical drug delivery system to enhance the skin permeation of active substance. So, the prime objective of this study was to develop a niosomal gel of fusidic acid to increase its skin permeation. Different formulations of niosomes of fusidic acid were designed by varying the cholesterol to surfactant ratio. Formulations containing fusidic acid, cholesterol, dihexadecyl pyridinium chloride, Span 60, or Tween 60 were prepared by thin film hydration method in rotary evaporator. The thin film formed in rotary flask was hydrated by phosphate buffer saline of pH 7.2. The niosomes formed were characterized through entrapment efficiency, size, polydispersity index (PDI), and zeta potential. The S3 formulation containing span 60 showed the highest entrapment efficiency (EE) of niosomes, so it was incorporated into Carbopol gel. Determination of pH, spreadability, rheological, and ex vivo permeation studies was conducted of niosomal gel. The results of ex vivo permeation studies showed high permeation of fusidic acid when gel was applied to an albino rat skin. According to the results and previous studies of niosomes, it can be concluded that niosomes enhanced the permeation of fusidic acid through the skin.